Additively manufactured multi-material free-form structure with printed electronics - Goh, Guo Liang (2019)
Additive manufacturing (AM) technique can help reduce time, cost, and complexity of the manufactured parts apart from adding functionality. This work explores AM techniques, namely fused deposition modeling (FDM) and PolyJet printing to fabricate a free-form structure with embedded electrical components. Both additive manufacturing technologies are discussed, analyzed, and compared. Another additive manufacturing method is then employed to print the electronic circuitry inside to connect the components. High-resolution X-ray computed tomography (CT) is employed to investigate the dimensional accuracy of the printed parts. This work demonstrates an innovative approach to construct arbitrary 3D objects with fully functional electronic circuits.